Students’ Perceptions of the Use of TOEFL Preparation Online Course on the Test Performance: The Case of TOEFL Structure and Written Expression Test - Sudrajat, Winny Nur Ardy; Astuti, Elysa Ratna (Bina Nusantara University, 2018)
This research aimed to investigate the use of an online TOEFL preparation course on the testperformance. The research method used was a quantitative method which emphasized on the objective measurements and the statistical analysis of collected data. The data were collected from the result of the online TOEFL test course program and the questionnaire to gain information about the students’ perception towards the use of online TOEFL preparation course on the test performance. The data were analyzed by using matchedtest to compare the result between the pre-test and the post-test. In addition, the means and percentages were used to analyze the questionnaire data to describe the students’ perception. The findings enrich theunderstanding on the use of TOEFL preparation program in improving TOEFL mastery on test performance.